Port designer's handbook - Thoresen, Carl A. (ICE Publishing, 2018)
Now in its fourth edition, 'Port Designer's Handbook' is the definitive guide to the layout, design and construction of harbours and port structures. Fully in line with the latest PIANC recommendations, this book covers all aspects of port planning and design from the impact of natural conditions on harbours, to health and safety, and the maintenance and repair of port structures as well as channel and harbour basins. Particular attention is given to the impact from ships, including berthing requirements, ship dimension tables and container terminals.